2022
DOI: 10.12963/csd.22886
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Children’s Temperament, Phonological Working Memory, Mother Related Factors, and Language Environment on Vocabulary Development in Korean Monolingual and English-Korean Bilingual Children

Abstract: Objectives: This study investigated the influence of internal and external factors on vocabulary development in Korean monolingual and English-Korean bilingual children, and examined predictors of their vocabulary skills.Methods: A total of 45 children aged from 3-6 years participated in this study, including Korean monolingual children (N= 30), and English-Korean bilingual children (N= 15). Children completed standardized vocabulary tests to measure vocabulary skills. To examine internal and external factors,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…In particular, we focused on heritage bilingual preschool children who learned Cantonese (HL) at home and were at the early stage of learning English (community language; L2) in school settings in the U.S. e unique linguistic contexts of heritage bilingual children present distinctive difficulties when it comes to expanding vocabulary knowledge and organizing semantic concepts (Sheng, 2014;Kang and Yim, 2021). Previous studies showed that semantic organization, which involves the interconnections of words and concepts, plays a crucial role in heritage bilingual children's language development (Sheng et al, 2013;Tong and Tong, 2022).…”
Section: The Current Studymentioning
confidence: 99%
“…In particular, we focused on heritage bilingual preschool children who learned Cantonese (HL) at home and were at the early stage of learning English (community language; L2) in school settings in the U.S. e unique linguistic contexts of heritage bilingual children present distinctive difficulties when it comes to expanding vocabulary knowledge and organizing semantic concepts (Sheng, 2014;Kang and Yim, 2021). Previous studies showed that semantic organization, which involves the interconnections of words and concepts, plays a crucial role in heritage bilingual children's language development (Sheng et al, 2013;Tong and Tong, 2022).…”
Section: The Current Studymentioning
confidence: 99%